Factors Influencing Work Motivation on Employee Performance - Dharma, Rifanny Ananta; Hirdanti, Dwi; Salianto, Salianto (Universitas Ibn Khaldun Bogor, 2024)
Employee performance is not just the final result, but a planned and measurable process over a certain period of time, in accordance with predetermined conditions and agreements. More than that, employee performance is a reflection of the way and how they carry out their duties, which is the main key in achieving organizational goals. This research uses a qualitative descriptive method and collects data from various relevant literature. The research results identified several factors that significantly influence employee motivation and performance. These factors include recognition, needs, achievement, satisfaction, compensation, leadership style, and work environment. By understanding and meeting these factors, organizations can create the right strategy to increase employee motivation and performance. This will ultimately have an impact on achieving more optimal organizational goals.